Biodegradable Fluorescent Nanoparticles for Endoscopic Detection of Colorectal Carcinogenesis. (10th October 2019) - Rogalla, Stephan; Flisikowski, Krzysztof; Gorpas, Dimitris; Mayer, Aaron T.; Flisikowska, Tatiana; Mandella, Michael J.; Ma, Xiaopeng; Casey, Kerriann M.; Felt, Stephen A.; Saur, Dieter; Ntziachristos, Vasilis; Schnieke, Angelika; et al.
Abstract: Early and comprehensive endoscopic detection of colonic dysplasia—the most clinically significant precursor lesion to colorectal adenocarcinoma—provides an opportunity for timely, minimally invasive intervention to prevent malignant transformation. Here, the development and evaluation of biodegradable near‐infrared fluorescent silica nanoparticles (FSN) that have the potential to improve adenoma detection during fluorescence‐assisted white‐light colonoscopic surveillance in rodent and human‐scale models of colorectal carcinogenesis is described. FSNs are biodegradable ( t 1/2 of 2.7 weeks), well‐tolerated, and enable detection and delineation of adenomas as small as 0.5 mm 2 with high tumor‐to‐background ratios. Furthermore, in the human scale, APC 1311/+ porcine model, the clinical feasibility and benefit of using FSN‐guided detection of colorectal adenomas using video‐rate fluorescence‐assisted white‐light endoscopy is demonstrated. Since nanoparticles of similar size (e.g., 100–150 nm) or composition (i.e., silica and silica/gold hybrid) have already been successfully translated to the clinic, and clinical fluorescent/white‐light endoscopy systems are becoming more readily available, there is a viable path towards clinical translation of the proposed strategy for early colorectal cancer detection and prevention in high‐risk patients. Abstract : Conventional white‐light colonoscopy has a relatively high adenoma miss rate, particularly in high‐risk patients. Biodegradable fluorescent silica nanoparticles (FSNs) have the potential to improve the detection of colorectal adenomas during endoscopic surveillance. Since FSNs are fully biodegradable and well‐tolerated, there is a viable path towards clinical translation of FSN‐guided colonoscopy for improved adenoma detection endoscopy in high‐risk patients.